2019
DOI: 10.1002/lary.28175
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossal Nerve Stimulator Outcomes for Patients Outside the U.S. FDA Recommendations

Abstract: Objectives The hypoglossal nerve stimulator (HGNS) is currently approved for the treatment of obstructive sleep apnea (OSA) in patients with an apnea‐hypopnea index (AHI) of >15 to ≤65 events/hour, and a central apnea index (CAI) <25% of the AHI, no complete concentric collapse on drug‐induced sleep endoscopy, and a recommended body mass index (BMI) <32 kg/m2. We present 18 patients implanted as a salvage procedure despite being outside these guidelines. Methods We included all patients who underwent HGNS but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
(41 reference statements)
1
25
1
Order By: Relevance
“…If Sher criteria 29 (50% reduction in AHI and overall AHI < 20) is used to define treatment response, an elevated AHI (more than 65) is not a HNS contraindication considering the reported treatment success in several studies, leading to a potential benefit for some patients with particularly severe disease. 30,31 On the other hand, also patients suffering from mild OSA could potentially benefit from HNS, 31 while some issues related to the invasiveness of the implanted device and the related patient discomfort should be taken into account to avoid patients' overtreatment. Moreover, HNS represents an expensive treatment with a cost of approximately 30.000 dollars per patient.…”
Section: Patient Selection and Efficacy Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…If Sher criteria 29 (50% reduction in AHI and overall AHI < 20) is used to define treatment response, an elevated AHI (more than 65) is not a HNS contraindication considering the reported treatment success in several studies, leading to a potential benefit for some patients with particularly severe disease. 30,31 On the other hand, also patients suffering from mild OSA could potentially benefit from HNS, 31 while some issues related to the invasiveness of the implanted device and the related patient discomfort should be taken into account to avoid patients' overtreatment. Moreover, HNS represents an expensive treatment with a cost of approximately 30.000 dollars per patient.…”
Section: Patient Selection and Efficacy Predictorsmentioning
confidence: 99%
“…On the other hand, some patients outside baseline inclusion parameters showed an optimal clinical response. 31 This clinical scenario should lead us to realize that OSA treatment could not be chosen on the basis of predetermined indications, while each patient should be assessed independently, trying to customize disease management based on several clinical aspects. HNS success is strictly dependent on a set of small factors that alone can greatly influence the clinical outcome.…”
Section: Hypoglossal Nerve Stimulation In the Era Of Precision Medicinementioning
confidence: 99%
“…Moreover, HGNS therapy was reported to be cost‐effective when compared with no treatment 8 . A very recent study 9 in patients outside the US Food and Drug Administration guidelines for HGNS revealed outcomes similar to those from the 1‐year STAR trial 5 …”
Section: Introductionmentioning
confidence: 95%
“…We initiated HGNS therapy in late 2014 at the Helsinki University Hospital. We used the same implantation device (upper Airway Stimulation system, Inspire Medical Systems, Maple Grove, MN, USA) as previously reported 3–10 . We applied the same inclusion and exclusion criteria, with the exception that we added a previous oral therapy failure to the inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglossal nerve stimulation (HGNS) is an established surgical treatment for refractory moderate‐to‐severe obstructive sleep apnea (OSA) in adults attributable to isolated tongue base collapse 1 . The indications for this procedure are continuing to expand, and a Food and Drug Administration (FDA) trial is currently underway evaluating the utility of HGNS in the Down syndrome population 2,3 . This population has a high incidence of refractory OSA that likewise is commonly due to isolated tongue base collapse 4 .…”
Section: Introductionmentioning
confidence: 99%